The advertisement call of Leptobrachella liui Fei and Ye, 1990 (Anura: Megophryidae) - Ding, Guo-Hua; Chen, Zhi-Qiang; Tang, Yun; Lin, Zhi-Hua (Zootaxa, 2019)
Leptobrachella (Anura: Megophryidae) is currently composed of seventy-one species distributed in China and Southeast Asia (Frost 2018). Fourteen species of Leptobrachella are currently known from southern China: L. alpina (Fei, Ye & Li, 1990), L. laui (Sung, Yang & Wang, 2014), L. liui (Fei & Ye, 1990), L. mangshanensis (Hou, Zhang, Hu, Li, Shi, Chen, Mo & Wang, 2018), L. maoershanensis (Yuan, Sun, Chen, Rowley & Che, 2017), L. oshanensis (Liu, 1950), L. purpura (Yang, Zeng & Wang, 2018), L. tengchongensis (Yang, Wang, Chen & Rao, 2016), L. wuhuangmontis (Wang, Yang & Wang, 2018), L. yingjiangensis (Yang, Zeng & Wang, 2018), L. yunkaiensis (Wang, Li, Lyu & Wang, 2018), L. ventripunctata (Fei, Ye & Li, 1990), L. pelodytoides (Boulenger, 1893) and L. sungi (Lathrop, Murphy, Orlov & Ho, 1998) and the first eleven species are endemic of this region (AmphibiaChina 2018). Many new species in this genus were discovered based on molecular, morphometric and bioacoustic data in recent years (Frost 2018). In comparison to molecular and morphological data, bioacoustics is especially useful in species identification of Leptobrachella in field surveys (Rowley et al. 2016). Although the advertisement calls of many Leptobrachella species were described along with the species descriptions (e.g., Rowley et al. 2016), the advertisement calls of only three Chinese endemic species (L. alpinus; L. laui and L. oshanensis) are known (Jiang et al. 2002; Matsui 2006; Xu et al. 2005). Here, we describe the advertisement calls of L. liui, which inhabits rocky streams in southeastern China (Fujian, Jiangxi and Zhejinag) and is morphologically diagnosed by the combination of a set of external color traits (Fig. 1).